E-Governance Philippine Information Agency (PIA) services through ICTS - Bernardo, Emmanuel R. (2013)
A government that is unified and accessible to the people is the primary goal of any government. Various types of government have tried this and failed miserably. But with the advancement of technology, a new avenue of governing was opened that made a unified government possible. With the emergence of Information and Communications Technology, new possibilities were opened that would help create better governance. With that, this study takes the opportunity to study how the Philippine government communicates with its people. This study primarily focuses on the concerns of sufficiency, efficiency, and effectiveness of the E-Governance program of the Philippine Information Agency. This research will be analyzed from the perspective of Information Specialists, its clients, and the staff of PIA in order to have a focused and reliable description, analysis and assessment of the policy.